Design and Construction of a Motor-Driven Conveyor Belt System. - Musiika, Justus (Kabale University, 2024)
This project aims to design and develop a low-cost and more efficient motor-driven conveyor belt system using materials such as the D.C motor, motor speed controller, switch, pieces of wood, connecting wires, and improvised rollers among others. The project aims to design and implement a small-scale conveyor belt system run by a DC motor for controlled material transportation. The system aims to demonstrate efficient and precise movement of small objects or components for small-scale industries, prototyping, or educational purposes. The system is equipped with a speed control, allowing for customizable transportation rates. The main focus of the project is on designing a motor-driven conveyor belt system, implementing DC motor control for adjustable speed, achieving reliable and precise material transportation, and evaluating system performance and efficiency. This small-scale project provides a foundation for understanding conveyor belt systems and DC motor control, with potential applications in larger industrial settings.